The expression of Lin28a in the ovaries and the association of Lin28a and Lin28b with litter size in goats - H. Liang; X. Du; Y. Xie; M. Chu; G. Cao (Archives Animal Breeding)
Lin28a and Lin28b serve as crucial regulators in gametogenesis. However, it remains unclear whether the two genes are expressed in goat ovarian tissues. In the present study, we examined the distribution of Lin28a proteins in the ovarian tissues of juvenile and pubertal Jining Grey (JG) goats. Additionally, we investigated the mutations in Lin28a and Lin28b and their association with litter size in JG goats. Lin28a proteins were predominantly expressed in the oocytes and granulosa cells of the follicles at different stages of development. Lin28a was also expressed in the corpus luteum, and its expression level declined as the corpus luteum formed and degenerated into the corpus albicans. A mutation (12298T>C) was identified in intron 2 of Lin28a, and there was no significant difference (P>0.05) in terms of the kidding number among the three genotypes of JG goats. For Lin28b, a mutation (718A>T) in exon 4 was found, presenting three genotypes. The frequency of genotypes AA, AT, and TT was 0.466, 0.504, and 0.03, respectively. The A allele was the dominant allele in JG goats, with an allele frequency of 0.718. At this locus, JG female goats with genotypes TT and AT had 0.83 (P<0.01) and 0.48 (P<0.05) more kids than the goats with genotype AA, and no significant difference (P>0.05) was observed in terms of litter size between the TT and AT genotypes. The present study preliminarily indicated an association between the T allele at the 718 locus in Lin28b and a larger litter size in JG goats. Moreover, Lin28a was widely expressed in follicles. These results suggest a potential DNA marker for improving the kidding number in goats and hold significance for goat breeding.